The role of symbiotic fungi in the life cycle of Gastrodia elata Blume (Orchidaceae): a comprehensive review - Liu, Jia-Jia; Yang, Xiao-Qi; Li, Zong-Yang; Miao, Jia-Yun; Li, Shi-Bo; Zhang, Wen-Ping; Lin, Yi-Cen; Lin, Lian-Bing (Frontiers in Plant Science, 2024)
Gastrodia elata Blume, a fully mycoheterotrophic perennial plant of the family Orchidaceae, is a traditional Chinese herb with medicinal and edible value. Interestingly, G. elata requires symbiotic relationships with Mycena and Armillaria strains for seed germination and plant growth, respectively. However, there is no comprehensive summary of the symbiotic mechanism between fungi and G. elata. Here, the colonization and digestion of hyphae, the bidirectional exchange of nutrients, the adaptation of fungi and G. elata to symbiosis, and the role of microorganisms and secondary metabolites in the symbiotic relationship between fungi and G. elata are summarized. We comprehensively and deeply analyzed the mechanism of symbiosis between G. elata and fungi from three perspectives: morphology, nutrition, and molecules. The aim of this review was to enrich the understanding of the mutualistic symbiosis mechanisms between plants and fungi and lay a theoretical foundation for the ecological cultivation of G. elata.